The impact of socioeconomic factors on pancreatic cancer care utilization - Masoud Khani; Mohammad Assadi Shalmani; Amirsajjad Taleban; Susan Tsai; Mochamad Nataliansyah; Mohammed Aldakkak; Jake Luo (PLoS ONE, 2025)
Background Pancreatic cancer carries a dismal prognosis, with socioeconomic factors significantly impacting patient outcomes. This study investigates the influence of socioeconomic determinants on access to specialized pancreatic cancer care and utilization rates in southeast Wisconsin. Methods We analyzed a dataset of 5,847 pancreatic cancer patients from the Froedtert & the Medical College of Wisconsin health system (2000-2023). Patient demographics were compared to the broader health system population. Utilization of specialized pancreatic cancer care was calculated for each patient’s zip code of residence. Linear and multivariate regression analyses were conducted to assess the association between socioeconomic factors (white population, income, education, insurance, Area Deprivation Index) and zip code-level utilization rates. Results Pancreatic cancer patients were older (mean age 66.3 vs. 46.5 years), predominantly male (52.7%), and disproportionately White (83.2% vs 63.6%) compared to the general population. Notably, patients residing in zip codes with the lowest median household income (<$42,000) had a 0.15% utilization rate, while those in the wealthiest areas (>$87,000) showed a 0.14% rate. Interestingly, utilization dipped to its lowest point (0.068%) in areas with median incomes between $53,100-$59,300. Initial analysis suggested that higher education levels, private insurance, and higher median incomes were linked to increased utilization. However, after accounting for other factors, only the Area Deprivation Index (ADI) and the percentage of the White population remained significant predictors. Specifically, a one-unit increase in ADI (indicating greater neighborhood disadvantage) was associated with a 0.0015% decrease in specialized care utilization (p < 0.05). Similarly, a 1% increase in the White population within a zip code was linked to a 0.0014% reduction in utilization (p < 0.05). Conclusion Our findings reveal that neighborhood-level socioeconomic disadvantage, as captured by the ADI, is a strong independent predictor of reduced access to specialized pancreatic cancer care in southeast Wisconsin. Furthermore, factors such as education level, income, and insurance status are significantly associated with increased utilization of these vital services. These results underscore the urgent need for targeted interventions to address these inequities and ensure that all pancreatic cancer patients have equal access to potentially life-saving care, regardless of their socioeconomic background.